2022
DOI: 10.3389/feduc.2022.823895
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Comparative Judgment Scores: How Assessors Evaluate Aspects of Text Quality When Comparing Argumentative Texts

Abstract: The advantage of comparative judgment is that it is particularly suited to assess multidimensional and complex constructs as text quality. This is because assessors are asked to compare texts holistically and to make a quality judgment for each text in a pairwise comparison based upon on the most salient and critical differences. Also, the resulted rank order is based on the judgment of all assessors, representing the shared consensus. In order to be able to select the right number of assessors, the question i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…However, a recent meta-analysis on comparative judgement demonstrates that the format of the task (e.g., texts, images, video, or portfolios) hardly affects the level of reliability (Verhavert et al, 2019). It is also recommended to replicate the study with another sample of more experienced raters, even though previous studies showed no differences between student raters and more experienced raters for comparative judgement (Lesterhuis, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent meta-analysis on comparative judgement demonstrates that the format of the task (e.g., texts, images, video, or portfolios) hardly affects the level of reliability (Verhavert et al, 2019). It is also recommended to replicate the study with another sample of more experienced raters, even though previous studies showed no differences between student raters and more experienced raters for comparative judgement (Lesterhuis, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the total number of comparisons can be distributed among multiple raters, which decreases the workload per individual rater. Researchers have also shown that including multiple raters in a CJ session will increase the validity of the results, as the shared consensus of multiple raters appears to be a good reflection of all relevant aspects of the writing task (Jones & Alcock, 2014;Lesterhuis, 2018;Van Daal et al, 2019).…”
Section: Comparative Approaches To the Assessment Of Writingmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, Comparative Judgement has proliferated across many writing assessment contexts, including large-scale primary and secondary-level assessment (e.g., McGrane et al, 2018;Pollitt, 2012;Wheadon, Barmby, Christodoulou, & Henderson, 2020), primary-level classroom-based assessment (e.g., Heldsinger & Humphry, 2010, 2013Humphry & Heldsinger, 2019b), higher education contexts (e.g., Lesterhuis, Bouwer, van Daal, Donche, & De Maeyer, 2022;van Daal, Lesterhuis, Donche, De Maeyer, & Coertjens, 2019), English as an additional language writing contexts (e.g., Şahin, 2021;Sims, Cox, Eckstein, Hartshorn, Wilcox, & Hart, 2020), as well as for the longitudinal equating of a standardised writing assessment (Humphry & McGrane, 2015).…”
Section: Educational Applications Of Comparative Judgementmentioning
confidence: 99%
“…In comparison to the issue of reliability, the validity of Comparative Judgement has much less attention, although there has recently been a proliferation of research focused on this issue (e.g., Chambers & Cunningham, 2022;Humphry & Heldsinger 2019a;Lesterhuis et al, 2022;Mentzer, Lee, & Bartholomew, 2021;van Daal, Lesterhuis, Coertjens, van de Kamp, Donche, & De Maeyer, 2017;van Daal et al, 2019). Typically, the method has been found to have moderate to high levels of concurrent validity with other more established methods like rubric-based ratings (e.g., Attali et al, 2014;Heldsinger & Humphry, 2010, 2013McGrane et al, 2018).…”
Section: Reliability and Validity Of Comparative Judgementmentioning
confidence: 99%